Islamic Education: Its Concepts and Their Implementation in the Current Context - Syihabuddin Syihabuddin; Aam Abdussalam (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2015)
Abstract The research discusses the concept and strategies of Islamic Education and their implementations in a global context. It aims to formulate concepts of contextual Islamic education implemented in higher education institutions in Indonesia, with the expectation that it will contribute to the solving of moral crisis currently experienced by Indonesia. In order to meet the aim, a mixed of quantitative and qualitative approaches was employed, with explanatory design. Data were collected from 54 lecturers and experts of Islamic education. The research has successfully formulated that a Muslim has to be educated by ethical teachers with exemplary method, scientific method, and ijtihâd method through the development of al-akhlâq al-karîmah course content, critical thinking skills, and development of democratic and universal values, supported by information and communication technology and evaluated with an authentic approach. These findings ascertain educators on the importance of al-akhlâq al-karîmah content, the teachers as role models, and the revitalization of ijtihâd tradition in the classroom. Abstrak Penelitian ini membahas konsep dan strategi Pendidikan Islam dan implementasinya dalam konteks global. Hal ini bertujuan untuk merumuskan konsep pendidikan Islam kontekstual untuk diterapkan di lembaga pendidikan tinggi di Indonesia, harapannya penelitian ini akan memberikan kontribusi pada penyelesaian krisis moral saat ini dialami Indonesia. Dalam rangka memenuhi tujuan penelitian, pendekatan campuran dari kuantitatif dan kualitatif diterapkan, dengan desain explanatory. Data dikumpulkan dari 54 dosen dan ahli pendidikan Islam. Penelitian ini telah berhasil merumuskan bahwa seorang Muslim harus dididik oleh guru yang berakhlak dengan metode teladan, metode ilmiah, dan metode ijtihad. Metode tersebut dirumuskan melalui pengembangan al-akhlaq al-karimah tertentu, keterampilan berpikir kritis, dan pengembangan nilai-nilai demokrasi dan nilai-nilai universal. Selain itu, metodenya didukung oleh teknologi informasi dan komunikasi. Selanjutnya, metode ini dievaluasi dengan pendekatan otentik. Temuan ini mengarahkan dengan pasti kepada pendidik tentang pentingnya konten al-akhlaq al-karimah, guru sebagai model peran, dan revitalisasi tradisi ijtihad di kelas. How to Cite: Syihabuddin., Abdussalam, A,. (2015). Islamic Education: Its Concepts and Their Implementation in the Current Context. TARBIYA: Journal Of Education In Muslim Society, 2(1), 23-34. doi:10.15408/tjems.v2i1.1436. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v2i1.1436